Relationship of Tissue Factor Pathway Inhibitor Activity to Plasma Lipoproteins and Myocardial Infarction at a Young Age - Moor, Elisabeth; Hamsten, Anders; Karpe, Fredrik; Båvenholm, Peter; Blombäck, Margareta; Silveira, Angela (Thrombosis and Haemostasis, 1994)
Tissue factor pathway inhibitor (TFPI) activity was quantified in two cohorts of young male post-infarction patients and in population-based control subjects to explore the relationships between TFPI activity and plasma lipoproteins and to address the issue of coordinate regulation of factor VII and TFPI in hyperlipidaemia and premature coronary heart disease (CHD). Participants were investigated in the fasting state and after an oral fat load. Basal TFPI activity and factor VII antigen (VIIag) levels were found to be increased in the patients (TFPI activity 1.25 ± 0.23 vs 1.17 ± 0.20 U/ml, p <0.05; VIIag 537.7 ± 127.7 vs 479.4 ± 93.4 ng/ml, p <0.001). The parallel increase was accounted for by patients with hypertriglyceridaemic lipoprotein phenotypes. In contrast, the level of activated factor VII (VIIa) neither differed significantly between patients and controls, nor between patients with different lipoprotein phenotypes. The elevated TFPI activity in the patients was closely associated with the plasma level of dense low density lipoprotein (LDL) particles (r = 0.46, p <0.001) and with the plasma concentration of the small, dense high density lipoprotein (HDL) subspecies HDL3b (r = 0.34, p <0.01).